A Study of the Thermal Decomposition of Wastewater Sludge Using Gas Chromatography - Maryandyshev, P. A.; Kangash, A. I.; Pokryshkin, S. A.; Lyubov, V. K.; Trouve, G.; Brillard, A. (Solid fuel chemistry, 2022)
The process of the thermal decomposition of the samples of mixed industrial and municipal wastewater sludge was investigated using gas chromatography. The composition of pyrolysis products obtained at temperatures of 200, 250, 300, 400, 500, and 600°C was determined. The groups of organic compounds detected in the pyrolysis products were analyzed. The temperatures of the onset of the release of volatile organic components and the highest heat release were determined.